AGROTECHNOLOGY FOR PRODUCING HIGH YIELDS OF VEGETABLE CROPS IN THE KHMER ROUGE REGION (Academicia Globe: Inderscience Research, 2023)
This article provides information on the agricultural technique of cultivating turnips from vegetable crops, it includes information on planting methods and techniques, seed germination temperature, the order of watering and fertilizing.